Increased body iron stores in elite road cyclists - Deugnier, Y.; Loreal, O.; Carré, F.; Duvallet, A.; Zoulim, F.; Vinel, J. P.; Paris, J. C.; Blaison, D.; Moirand, R.; Turlin, B.; Gandon, Y.; David, V.; et al. (Medicine & Science in Sports & Exercise, 2002)
BACKGROUND: One third of French elite road cyclists were found to have hyperferritinemia on antidoping control tests performed during the Tour de France in 1998. PURPOSE: This study was undertaken to determine whether hyperferritinemia corresponded to elevated body iron stores or not and, affirmatively, what were its mechanism, its clinical consequences, and its spontaneous course. METHODS: 83 elite road male cyclists presenting with hyperferritinemia, defined as serum ferritin level greater than 300 microg.L-1, were studied with respect to consumption of iron and other drugs, serum iron tests, HFE mutations, and hepatic iron concentration (HIC; N < 35 micromol.g-1 dry weight). RESULTS: All cyclists were asymptomatic and had normal physical and cardiac examination. Their median (range) serum ferritin, serum iron, and transferrin saturation levels were 504 microg.L-1 (306-1671), 20 micromol.L-1 (8.5-36.3), and 39% (20-76), respectively. HIC was increased in 24/27 up to 187 micromol.g-1. Allelic frequency of the H63D mutation was increased in cyclists when compared to controls (P = 0.04). However, iron tests did not differ according to HFE genotypes. Most cyclists (89%) had been supplemented with iron. The median iron supplementation was 25.5 g (range: 1.4-336) and correlated well (P = 0.002) with serum ferritin. Evolution of serum ferritin levels did not differ whether cyclists had been continuing iron supplementation or not. CONCLUSION: Hyperferritinemia in elite road cyclists accounted for increased body iron stores caused by and persisting after cessation of excessive iron supplementation. Even when mild, iron excess may expose to long-term complications and should be removed, at least at the time when professional cyclists retire. To prevent iatrogenic iron overload, supplementation with iron must be done according to serum ferritin follow-up and not either blindly or on the basis of serum iron determination only.